Coupled heating/acidification pretreatment of chemical sludge for dewatering by using waste sulfuric acid at low temperature. (August 2018) - Bian, Bo; Zhang, Limin; Zhang, Qin; Zhang, Shaopeng; Yang, Zhen; Yang, Weiben
Abstract: A cost-effective approach for pretreatment of chemical sludge for further dewatering, based on the idea of "using waste to treat waste", is provided. It is a coupled heating/acidification pretreatment method, where waste sulfuric acid is employed and relatively low temperatures (<100 °C) are applied. Effects of reaction time, temperature, and dosage of waste acid on dewatering performance (both dewatering speed and degree) are studied. Under the optimal conditions (reaction time: 30 min; temperature: 90 °C; waste acid dosage: 0.175 g/(g dried sludge)), the method of this work demonstrates three advantages compared to the conventional method using lime+polyacrylamide: lower moisture content of treated sludge; higher calorific value for incineration process; and lower cost. Detailed mechanism of the pretreatment for dewatering is investigated via characterizations and statistical analyses of various parameters, among which zeta potential, particle size, protein and polysaccharide contents, soluble chemical oxygen demand (SCOD), reduction of combined water and volatile suspended solid (VSS), are associated with dewatering performance. Both heating and acidification generate disintegration of cells in sludge, giving rise to two phenomena: more organic matters are released into solution and more bound water turns into free water. Meantime, the released organic polymers flocculate sludge particles, further accelerating the solid-liquid separation process. Graphical abstract: Image 1 Highlights: Pretreatment methods with low energy-consumption and economic cost are needed. Pretreatment of sludge using waste sulfuric acid at low temperature is performed. Such a method shows better performance than conventional one. Microscopic dewatering mechanism is investigated in detail.